2013
DOI: 10.1007/s00464-013-3163-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of laparoscopic versus robot-assisted colorectal resection

Abstract: RALR had significantly higher costs and operative time than traditional LAP without a measurable benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 50 publications
1
44
1
Order By: Relevance
“…None of these studies included the robot capital cost, time-horizon beyond hospitalisation time and utility measurements. A similar approach was used in the study that reported on resection of the rectum [43]. This study has reported higher total costs for RAL surgery (US$24,531) compared with laparoscopy (US$19,269).…”
Section: Colectomymentioning
confidence: 81%
See 2 more Smart Citations
“…None of these studies included the robot capital cost, time-horizon beyond hospitalisation time and utility measurements. A similar approach was used in the study that reported on resection of the rectum [43]. This study has reported higher total costs for RAL surgery (US$24,531) compared with laparoscopy (US$19,269).…”
Section: Colectomymentioning
confidence: 81%
“…Colectomy costs were reported in three studies that all identified RAL (range US$15,869-$20,555) to have higher total cost than laparoscopy (range US$12,790-$16,896) [27,42,43]. None of these studies included the robot capital cost, time-horizon beyond hospitalisation time and utility measurements.…”
Section: Colectomymentioning
confidence: 96%
See 1 more Smart Citation
“…Some studies have compared the feasibility and efficacy of robotic surgery with that of laparoscopic surgery for the treatment of colorectal cancer [14][15][16]. However, no studies have compared patients' perioperative immune status after robotic, laparoscopic, and open colorectal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies analyzing a large-scale clinical database, a clinical benefit cannot be confirmed with robot-assisted colorectal resection, and it is reported that robotic surgery comes along with significantly higher costs compared to laparoscopic surgery [9][10][11]. Moreover, in the ROLARR (RObotic Versus LAparoscopic Resection for Rectal Cancer) trial, which attracted attention as a high-quality multicenter prospective randomized controlled trial comparing robotic rectal resection for rectal cancer with laparoscopic resection, there was no statistically significant difference regarding conversion rate to open surgery, configured as a primary endpoint, as well as in bladder dysfunction, sexual function, and pathological resection margin positivity [30].…”
Section: Discussionmentioning
confidence: 99%